ВПЛИВ НЕСПЕЦИФІЧНИХ ЗАХВОРЮВАНЬ ОРГАНІВ ДИХАННЯ НА СТАН ТКАНИН ПАРОДОНТА У ДІТЕЙ - Шило, М. М.; Януш, В. Я. (Українські медичні вісті, 2023)
ВПЛИВ НЕСПЕЦИФІЧНИХ ЗАХВОРЮВАНЬ ОРГАНІВ ДИХАННЯ НА СТАН ТКАНИН ПАРОДОНТА У ДІТЕЙ